2009
DOI: 10.1124/jpet.108.145466
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2Derived from Cyclooxygenases 1 and 2 Mediates Intestinal Epithelial Ion Transport Stimulated by the Activation of Protease-Activated Receptor 2

Abstract: Proteinase-activated receptor (PAR) 2 is activated by trypsinlike serine proteinases and has been implicated in intestinal inflammation. However, its role in the regulation of intestinal mucosal function remains unclear. Using the intestinal epithelial cell line, SCBN, we have studied the stimulus-secretion coupling mechanisms of PAR 2 -induced epithelial chloride transport, focusing on cyclooxygenase (COX)-1 and COX-2 activities and prostaglandin (PG) E 2 secretion. SCBN monolayers were grown on Snapwell supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…21 Therefore, we evaluated the effects of AH6809, an antagonist of DP 1 , EP 1 , and EP 2 receptors. [22][23][24] Interestingly, we found that the responses to Tam or its metabolites in the presence of AH6809 were very similar to those found in the presence of the COX inhibitor indomethacin. Taken together, these results provide strong evidence supporting the idea that Tam and its metabolites induce vasorelaxation by promoting the synthesis of vasodilator prostanoids.…”
Section: Discussionsupporting
confidence: 67%
“…21 Therefore, we evaluated the effects of AH6809, an antagonist of DP 1 , EP 1 , and EP 2 receptors. [22][23][24] Interestingly, we found that the responses to Tam or its metabolites in the presence of AH6809 were very similar to those found in the presence of the COX inhibitor indomethacin. Taken together, these results provide strong evidence supporting the idea that Tam and its metabolites induce vasorelaxation by promoting the synthesis of vasodilator prostanoids.…”
Section: Discussionsupporting
confidence: 67%
“…More recently, experiments in an intestinal epithelial cell line mounted in Ussing chambers revealed that basolateral protease-activated receptor-2 (PAR-2) activation induces CFTR-mediated chloride secretion by PGE 2 confirming the general applicability of this mechanism, which has previously been noted to be the likely explanation for PGE 2 -and PGF 1 -mediated stimulation of chloride secretion by PAR-2 activation [152].…”
Section: Ion Channels Regulating Fluid Distributionmentioning
confidence: 82%
“…The activation of PAR2 has further been associated with a rapid cellular release of a series of agonists triggering the immediate autocrine or paracrine transactivation of other non-PAR G protein-coupled receptors, including prostanoid receptors [23]. Further supporting a PAR2-dependent release of prostanoids, a few reports have linked PAR2 activation with enhanced COX2 activity and expression not only in endothelial cells but also in other cell types, including mesangial or mast cells [27][28][29]. TXA 2 is a powerful vasoconstrictor and aggregating factor with proinflammatory properties in the cardiovascular system, whose overproduction is associated with disturbed vascular function in different conditions including aging and diabetes [13,15].…”
Section: Discussionmentioning
confidence: 97%